PENGARUH PSIKOEDUKASI EMPATI DALAM MENINGKATKAN PERILAKU TOLERANSI SISWA SD NEGERI TUGU SURAKARTA - Fitriani, Aulia Endah; Andayani, Tri Rejeki (JPI (Jurnal Pendidikan Inklusi), 2024)
Tolerance behavior is important in inclusive schools so that the goals of inclusive schools can berealized. However, intolerant behavior is still found at inclusive schools, so it needs to beaddressed, and empathy is one of the factors. This research aims to determine the effect ofempathy psychoeducation through fairy tales on the tolerance behavior of students at inclusiveelementary school X. The research used a pre-experimental method with a one-group pretestposttest design. The research sample was 50 students from Grades 2 to 6 of inclusive elementaryschool X who were obtained through a purposive sampling technique with the criteria for a pretestscore on tolerance behavior in the low category and were willing to become participants. Datawere collected using the Tolerance Behavior Questionnaire (Reliability 0.722). Data analysisused the Wilcoxon Test with IBM SPSS Statistics 25. The results obtained a Sig. (1-tailed) valueof 0.030 (p <0.05). Psychoeducation through fairy tales has a positive influence on the tolerancebehavior of students of inclusive elementary school X. Further research can add a control groupso that external variables can be more controlled and the research results become more accurate.